Clinical and functional outcomes of open versus minimally invasive surgeries in single-level prolapsed intervertebral disc in lumbar region at tertiary care center: A prospective study - Jolly Sinha; Vivek Kumar Kankane; Avdhesh Shukla; Avinash Sharma (Asian Journal of Medical Sciences, 2023)
Background: Spine surgery has been transformed significantly by the growth of minimally invasive surgery (MIS) procedures. Modern MIS techniques allow spine surgeons to achieve the same goals of open surgery while minimizing the collateral damage associated with the open approaches. Aims and Objectives: The aim of MIS is to do an efficient “Target Surgery” with a minimum of iatrogenic trauma. Materials and Methods: This is a prospective study done in the Department of Neurosurgery, JA group of hospitals, Gajra Raja Medical College, Gwalior, from July 2021 to July 2022. Study was conducted on 30 randomly selected patients whose presentation and imaging showed indication for surgery. Results: Better symptomatic relief was seen in patients with MIS at 7 days with about 80% of them having a visual analog scale score between 0 and 2; however, not much difference was noted at 1 month. Not much difference was noted for wound status, neurological improvement, and Oswestry Disability Index at 1 month. However, gross difference was noted at the rate of return to work by the patients with approximately 93.3% of patients undergoing MIS returning to work within 1 month in comparison to only 20% in case of open surgery. Conclusion: Minimally invasive techniques are remarkably better option to traditional open surgeries, as these procedures showed a significant reduction in immediate post-operative pain, duration of hospital stay, and return to work by the patient. However, not much difference was noted in status of pain at 1 month, rehospitalization, degree of disability at 1 month, wound status, and neurological improvement of the patient.